Three scleral ossicles in the West African Denticle herring Denticeps clupeoides (Clupeiformes: Denticipitidae). Issue 3 (9th February 2022) - Kubicek, Kole M.; Britz, Ralf; Pinion, Amanda K.; Bower, Luke M.; Conway, Kevin W.
Abstract: The eyes of teleostean fishes typically exhibit two ossifications, the anterior and posterior sclerotics, both associated with the scleral cartilage. The West African Denticle herring Denticeps clupeoides has three scleral ossifications, including the typical two associated with the scleral cartilage (anterior and posterior sclerotic) and a third ossification (Di Dario's ossicle), spatially separated from the scleral cartilage and located within the anteromedial wall of the sclera. The medial rectus muscle inserts on the medial surface of Di Dario's ossicle, suggesting that this third sclerotic may play a role in forward rotation of the eye in this surface feeding fish.